Dahrendorf e Habermas. Un sodalizio intellettuale - Corchia, Luca (SocietàMutamentoPolitica, 2019)
The essay describes some crucial moments in the intellectual biography of Ralf Dahrendorf and Jürgen Habermas, focusing on their frequent relationships in the first forty years. This research shows that, beyond the many divergences, what linked them in an enduring sodality was a radically democratic orientation that was consolidated in some epochal caesuras of German history: the advent of the Third Reich, the Second World War and the Anglo-American liberal “re-education”, the “normalization” of the Adenauer era, the crisis of democracy and the protest of the “Sixty-eight”.